Potencial da fibroína de seda na engenharia do tecido pulpar - Klein, Elen Mariane Dal Bosco (2019)
Bioengineering studies the incorporation of natural alternative materials that exhibit excellent biocompatibility, bioactivity, absence of toxicity and physical properties that simulate the environment in vivo, favoring the repair, replacement or improvement of damaged tissues. A protein from the cocoon of the silkworm, fibroin, has shown promising results in healing, regeneration and attenuation of the inflammatory response in recent research, and has been mentioned as an excellent substitute for collagen. Its properties allow growth of neurons and axonal connections. These functions create a new use option for this material produced in large scale in Brazil. Tissue engineering emerges as an alternative to the usual treatment and can create a new protocol incorporating fibroin among materials of applications in dentistry, aimed at regeneration and non-repair. There is evidence that fibroin is a safe and efficient scaffold, having mechanical and biological properties that represent a possibility of tissue regenerator for dental use to constitute a viable alternative in the treatment of pulp exposures. The objective of this work was to compile, organize and present scientific articles published in literature databases that tested the silk fibroin in tissues and / or cells compatible with that found in the dentin / pulp complex, including studies that analyzed its interaction with several living tissues, aiming at those with similarities to those found in the pulp: bone, loose connective, nervous, in addition to isolated cells: fibroblasts and osteoblasts. This is a bibliographical review based on journals researched in the following databases: Latin American and Caribbean Literature in Health Sciences (LILACS), Brazilian Bibliography of Dentistry (BBO), Scientific Electronic Library Online (SCIELO), Medical Literature Analysis and Retrieval System Online (MEDLINE) and Portal CAPES, in the period of March 2017 June 2019. The literature has presented a consistent scientific basis of the regenerative potential of fibroin and the need for research to be carried out for comparison and possible effectiveness of the same as an alternative among the options of dental materials with great biological potential.